Preparação de filmes poliméricos biodegradáveis para a aplicação em embalagens para cosméticos - Dias, Lucas Weber (2017)
The main function of the packaging is to protect the cosmetic from the external environment, avoiding undesirable changes in the product that is contained inside, and thus indispensable for its storage and transpotation. However, its disposal improperly generates a large volume of solid waste, which is directly related to the environmental impact. One of the alternatives to minimize this impact is the use of packages made from biodegradable polymeric films based on polyacrylic acid (PLA), poly (lactic acid – co- glycolic acid) (PLGA) and polycaprolactone (PCL), blends of theses polymers and incorporation of Zeolites 13x. The thermal, mechanical optical, water vapor barrier and degradation time in saline solution of polymeric systems are evaluated for application as cosmetic packaging. The technique used for the preparation of the polymer films was that of Solvent Casting. The polymer films were characterized by the techniques of UV-Vis Spectrophotometry, Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), Scsannig Electron Microscopy (SEM), transparency, water vapor permeability, mechanical assay and absorption spectroscopy atomic. The transmittance results showed that the PCL and PLA blends showed greater blockage to the passage of radiation (190 - 1100nm) and water vapor permeability. The incorporation of PLA or PLGA to the pure PCL resulted in material with batter thermal properties, but more rigid and brittle, not modifying the degradation process until 120 days of incubation. The incorporation of 15% Zeolite 13x into the PCL/PLA blends did not significantly modify the properties evaluated.